Thermally Activated Natural Clay for the Removal of Pharmaceutical Drug Levofloxacin - KULKARNI, RAVIRAJ M.; YAKKERIMATH, SHILPA; V. DIVEKAR, SANJAYKUMAR; CHATE, VAIBHAV R.; PURANDARA, BEKAL (Asian Journal of Chemistry, 2023)
The adsorption behaviour of natural clay (NC) and thermal activated clay (TAC) mineral of the Panchanganga river flood zone sediment for levofloxacin (a class of fluoroquinolone antibacterial drug) has been studied. The isotherm and kinetic studies were performed using the batch technique. The results showed that TAC has 72.6% removal efficiency comparatively higher than NC, which is 62.8% at 120 min, pH = 7, dosage 0.40 g/L and Initial concentration of 18.69 mg/L. The kinetic and isotherm results indicate the adsorption of levofloxacin on NC and TAC follows Freundlich isotherm suggesting multilayer sorption and chemisorption as a rate-limiting step during the process. A plausible mechanism is proposed for the interaction of NC and TAC with levofloxacin from the results of the adsorption study. The negative free energy change and positive enthalpy change indicated that the adsorption process is spontaneous and endothermic.